Molecular Characteristics of Streptococcus pyogenes Isolated From Chinese Children With Different Diseases - Yu, Dingle; Liang, Yunmei; Lu, Qinghua; Meng, Qing; Wang, Wenjian; Huang, Lu; Bao, Yanmin; Zhao, Ruizhen; Chen, Yunsheng; Zheng, Yuejie; Yang, Yonghong (Frontiers in Microbiology, 2021)
Streptococcus pyogenes is a bacterial pathogen that causes a wide spectrum of clinical diseases exclusively in humans. The distribution of emm type, antibiotic resistance and virulence gene expression for S. pyogenes varies temporally and geographically, resulting in distinct disease spectra. In this study, we analyzed antibiotic resistance and resistance gene expression patterns among S. pyogenes isolates from pediatric patients in China and investigated the relationship between virulence gene expression, emm type, and disease categories. Forty-two representative emm1.0 and emm12.0 strains (n = 20 and n = 22, respectively) isolated from patients with scarlet fever or obstructive sleep apnea-hypopnea syndrome were subjected to whole-genome sequencing and phylogenetic analysis. These strains were further analyzed for susceptibility to vancomycin. We found a high rate and degree of resistance to macrolides and tetracycline in these strains, which mainly expressed ermB and tetM. The disease category correlated with emm type but not superantigens. The distribution of vanuG and virulence genes were associated with emm type. Previously reported important prophages, such as φHKU16.vir, φHKU488.vir, Φ5005.1, Φ5005.2, and Φ5005.3 encoding streptococcal toxin, and integrative conjugative elements (ICEs) such as ICE-emm12 and ICE-HKU397 encoding macrolide and tetracycline resistance were found present amongst emm1 or emm12 clones from Shenzhen, China.